Features that should be paid attention to when teaching Russian at a pedagogical institute (Journal of Pedagogical Inventions and Practices, 2022)
The formation of innovative competencies among modern teachers is one of the urgent requirements of education. The teacher's time and effort required to put new ideas and methods into practice depends on the teacher and his or her training.